Synthesis and performance of a novel high-efficiency coal dust suppressant based on biopolysaccharide-xanthan gum - Gan, Jian (2022)
The coal production process produces a lot of dust, which pollutes the environment and threatens the occupational health of workers. Although many dust suppressants for coal dust control have been developed, the implementation of current dust suppressants does not meet the requirements due to their poor foaming, stability, and wettability effects. In our current study, the effect of xanthan gum (XG) on the properties and foaming ability of the composite surfactant ALAP has been investigated. The research shows that with the increase of CXG, the foaming volume of the solution increases by nearly 30% on average. The liquid-carrying capacity, the foaming delay period, and the liquid-draining half-life of the foam are also improved, while the performance of wetting coal dust decreases. Compared with traditional water-soluble polymers, XG molecules have a special double helix structure and plenty of polar functional groups, which can form a stable 3D network system with surfactant molecules. XG molecules could not only effectively improve the foaming performance of low-concentration ALAP, the liquid-carrying ability, and the stability of foam, but also reduce the burst rate of the bubbles. In our investigations, the dust reduction effect of the XG/ALAP systems have been comprehensively evaluated through the field application of the heading face. The dust reduction efficiency of total dust and respirable dust can reach nearly 90% and 85% respectively, which is 2.2 times and 2.5 times higher than that of water spraying. The XG/ALAP systems also effectively improve the visibility of the working surface. With the consideration of all the above-mentioned factors, the composition range of the high-efficiency dust suppressant is obtained as: 0.7‰≥CXG ≥ 0.5‰ and 4‰≥CALAP ≥ 3‰.